Organization of Medical Care to Children with Road Traffic Injury in the Rostov Region - I.I. Babich; T. V. Vygonskaya; F. G. Sharshov; Ye. A. Spiridonova; S. A. Rumyantsev; E. E. Rostorguyev (Общая реаниматология)
Objective: to analyze the efficiency of the Rostov Region’s medical care service for children with severe traumatic injuries due to road traffic accidents. Results. It has been established that the service meets the generally accepted stepwise principles and has a multilevel network of hospitals, which allows the earliest performance of the required volume of medical care in relation to the pattern and severity of lesions. It has been shown that 58.3% of the children with severe traumatic lesions are primarily admitted to the central district hospitals and emergency care ones that are aimed at rendering medical aid to the adult population. Thus, medical care is delivered to the above contingent by non-pediatric surgical and resuscitative-anesthetic services. Conclusion. By keeping in mind the specific features of the emergency medical system existing in the region, the authors propose its further development, by organizing interregional centers on the basis of a number of central regional hospitals for the treatment of children with traumatic lesions (among other things, by allocating pediatric beds in the intensive care units). The stepwise solution of this problem is currently being done in the Rostov Region in two main directions: 1) organization by developing a round-the-clock advisory subdivision (with an exiting sanitary aviation team) on the basis of – the regional children’s clinical hospital and 2) methodical maintenance of multidisciplinary h°spitals in delivering medical care to different age-groups children. Key words: road traffic accidents, emergency medical service, children, traumatic lesions.